A Secure Communication with One Time Pad Encryption and Steganography Method in Cloud - et. al., Lalit Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing is a framework for suitable on demand network admittance to a mutual pool of computer resources. Cloud computing is a model for delivering services as per the demand related to information technology over the internet. It is a type of internet-based computing by which client pay for using the services. A client sends a request to the cloud server, server respond to his request and deliver on demand services. The inflamed attack in the cloud surface makes it extra susceptible to prevailing and emerging security threats. Predictable cloud data prevention and security approached have been initiated unable in anticipation of such threats and this distasteful trend has compelled the need of revolutionary approach to cloud data security. Blowfish Encryption and Steganography already had established techniques of data security. This Research work possess an amplify approach to safeguarding data security by combining both of the proven techniques. The united methodology is aimed to leveraging the strength of these